2017
DOI: 10.3892/or.2017.5853
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of MUC4 potentiates the anticancer activity of auranofin via regulation of the Her2/Akt/FOXO3 pathway in ovarian cancer cells

Abstract: Previously, we reported that auranofin induces apoptosis in SKOV3 cells via regulation of the IKKβ/FOXO3 pathway. In the present study, we reveal that the anticancer activity of auranofin in SKOV3 cells could be enhanced by the attenuation of MUC4 through the regulation of the Her2/Akt/FOXO3 pathway. Compared to the control-siRNA, siRNA transfection against MUC4 into SKOV3 cells accelerated the protein degradation of Her2. Under the same conditions, the expression level of phosphorylated Akt was also downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Additionally, MUC4 has been shown to reduce the interactions between cells, promote cell separation, and promote tumor metastasis (30,50). AFPR was reported to phosphorylate a 185-kDa ErbB2 protein (30), while MUC4 can bind to 185-kDa ErbB2 and induce phosphorylation of ErbB2 at the 1139Y and 1248Y sites, which results in activity of AKT and its related signaling pathways leading to promotion of cell survival (30,(80)(81)(82). MUC4 is highly expressed in breast cancer, and AFPRs were first isolated from the human MCF-7 breast cancer cell line (30).…”
Section: Mucin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, MUC4 has been shown to reduce the interactions between cells, promote cell separation, and promote tumor metastasis (30,50). AFPR was reported to phosphorylate a 185-kDa ErbB2 protein (30), while MUC4 can bind to 185-kDa ErbB2 and induce phosphorylation of ErbB2 at the 1139Y and 1248Y sites, which results in activity of AKT and its related signaling pathways leading to promotion of cell survival (30,(80)(81)(82). MUC4 is highly expressed in breast cancer, and AFPRs were first isolated from the human MCF-7 breast cancer cell line (30).…”
Section: Mucin Receptorsmentioning
confidence: 99%
“…Both receptor proteins are highly glycosylated with multiple O-linked glycans. Therefore, MUC4 may also be a viable candidate for an AFP receptor ( 9 , 30 , 82 , 83 ).…”
Section: Mucin Receptorsmentioning
confidence: 99%
“…FOXO3 is known as a tumor-inhibitive transcriptional factor and interacts with serine/threonine protein kinase (AKT) in OC. 11 Shen et al. asserted the notion that miR-29a contributes to the drug resistance observed in breast cancer cells through the AKT/glycogen synthase kinase 3β (GSK3β) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the phosphorylation of Ser318 by Akt induces the subsequent phosphorylation of Ser322 by casein kinase 1, which is critical for translocation of FOXO3 from the nucleus into the cytosol. In previous studies ( 11 , 12 , 23 ), attempts were made to develop a novel cell-based ELISA assay system using a phospho-FOXO3 antibody to screen small molecules causing nuclear localization of FOXO3. Following testing various commercially available phospho-FOXO3 antibodies including pThr32 and pSer253, which are possible Akt-phosphorylation sites identified by Brunet et al ( 10 ), pSer318/321 FOXO3 antibody was selected as the best antibody for the cell-based ELISA system, due to a larger difference in the readout value being detected between the positive controls (Wortmannin and LY294002) and the negative control.…”
Section: Resultsmentioning
confidence: 99%